2011
DOI: 10.1130/g32073.1
|View full text |Cite
|
Sign up to set email alerts
|

Aseismic sliding of active faults by pressure solution creep: Evidence from the San Andreas Fault Observatory at Depth

Abstract: Active faults in the upper crust can either slide steadily by aseismic creep, or abruptly causing earthquakes. Creep relaxes the stress and prevents large earthquakes from occurring. Identifying the mechanisms controlling creep, and their evolution with time and depth, represents a major challenge for predicting the behavior of active faults. Based on microstructural studies of rock samples collected from the San Andreas Fault Observatory at Depth (California), we propose that pressure solution creep, a pervas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
109
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(118 citation statements)
references
References 21 publications
9
109
0
Order By: Relevance
“…Dissolutione precipitation processes are operative during co-seismic and aseismic slip (Gratier and Gamond, 1990;Gratier et al, 2011;Chen et al, 2013). Pressure-solution seams and soluble minerals such as feldspar, quartz and calcite are present in SAFOD as well as TCDP samples.…”
Section: Dissolutioneprecipitation Processesmentioning
confidence: 99%
“…Dissolutione precipitation processes are operative during co-seismic and aseismic slip (Gratier and Gamond, 1990;Gratier et al, 2011;Chen et al, 2013). Pressure-solution seams and soluble minerals such as feldspar, quartz and calcite are present in SAFOD as well as TCDP samples.…”
Section: Dissolutioneprecipitation Processesmentioning
confidence: 99%
“…These initiatives have recovered samples of fault rock and gouge and conducted measurements of in situ stress, fluid chemistry, and temperature at depths where earthquakes nucleate. Samples and data emerging from these drilling projects provide an unparalleled opportunity to gain new insight into absolute fault strength [e.g., Brune et al, 1969;Zoback et al, 1987;Scholz, 2000;Carpenter et al, 2012], causes of apparent fault weakness [e.g., Rice, 1992;Faulkner and Rutter, 2001;Brantut et al, 2011;Gratier et al, 2011;Lockner et al, 2011], and the laws that govern fault slip and failure [e.g., Dieterich, 1979;Marone, 1998a;Ikari et al, 2009;Carpenter et al, 2011;Sone et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…The mineralogical assemblage is partially inherited from the host rock but displays a stronger fabric with well-expressed CS structures. Aseismic sliding of active fault by pressure solution creep has been well documented in the San Andreas Fault observatory at depth by Gratier et al (2011) who demonstrate that such mechanism can accommodate 20 mm/year sliding.…”
Section: Discussionmentioning
confidence: 99%
“…Takahashi et al 2007;Ikari et al 2011). In the San Andrea fault observatory at depth (SAFOD) core samples, the weakening of the San Andreas fault zone down to depths of at least 3 km is attributed to the pervasive development of interconnected networks of low friction smectitic phyllosilicates and to the operation of stress-induced solutionprecipitation creep mechanisms (Holdsworth et al 2011;Gratier et al 2011). Morrow et al (2000) have demonstrated that the frictional strength of clay minerals is inversely dependant on their capacity to adsorb water and therefore, may influence fault behaviour.…”
Section: Introductionmentioning
confidence: 99%